An example of comparison between ISO Norm calculations and full CFD simulations of thermal performances of hollow bricks. (May 2017) - Laaroussi, N.; Lauriat, G.; Raefat, S.; Garoum, M.; Ahachad, M.
Abstract: Coupled heat transfers by conduction, convection and radiation through hollow clay bricks are numerically investigated thanks to the use of CFD simulations based on a finite volume method. The heat flow is governed by the incompressible Navier-Stokes and energy equations. On account of the small temperature differences involved, the two-dimensional model is based on the Boussinesq approximation and constant thermophysical fluid properties at the mean temperature of the internal and external temperatures of the surroundings. The brick wall surfaces are assumed gray and diffuse and, the bottom and top horizontal walls are adiabatic. Comparisons between the brick thermal performances predicted by a 1D-approximate method and by the present 2D-numerical approach are shown in the form of Tables, maps of temperature and streamfunction, and temperature profiles. The discrepancies between the two calculation methods of the design thermal resistance and thermal transmittance are discussed and their origins explained. Abstract : Highlights: A numerical method is used to predict the thermal performances of hollow bricks. The conservation equations and the radiative exchanges amongst surfaces are solved. Comparison with the thermal resistance method is discussed for 6–16-holed bricks. The origins in the discrepancies between the two approaches are explained.